If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 90 = 10x + 120 Reorder the terms: 90 + 20x = 10x + 120 Reorder the terms: 90 + 20x = 120 + 10x Solving 90 + 20x = 120 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 90 + 20x + -10x = 120 + 10x + -10x Combine like terms: 20x + -10x = 10x 90 + 10x = 120 + 10x + -10x Combine like terms: 10x + -10x = 0 90 + 10x = 120 + 0 90 + 10x = 120 Add '-90' to each side of the equation. 90 + -90 + 10x = 120 + -90 Combine like terms: 90 + -90 = 0 0 + 10x = 120 + -90 10x = 120 + -90 Combine like terms: 120 + -90 = 30 10x = 30 Divide each side by '10'. x = 3 Simplifying x = 3
| 2x+10=50-8x | | 5+5x+1-3x=-4+6x+5-5x | | 60+42+x=180 | | -6/113/4 | | 448x^4-175x^2y^2= | | 42-5x=28-2x | | 15x^2-6x=153 | | 4k-3=7 | | 30+64=4x-6 | | 1.5X-6=50 | | 2-z=-2 | | 31/2x(1-3)^4 | | 8y-2y=60 | | 3x+7=28-2x | | 6(y-1)=2y+8 | | 4/53/8 | | 5x=12x-6x | | 0.25x+0.1y=1.8 | | 1/31/4 | | 9x-6l=-16 | | 0.8-4(b-1)=0.2+3(4-3) | | -4.9x^2+90x=0 | | (a+1)=9 | | 5/8/2/4 | | 5X+5H+1-(5X+1)= | | 2x^2+2xy-3y^2=2 | | 2x+95=6x+43 | | 3.5Y+5=13.5Y+14 | | 7x-2=8x+17 | | x^4-6x^3+12x^2-4x-1=0 | | 65=v/5 | | 3(x+6)=6(x-3)+x |